Inorganic Membranes: Preparation and Application for Water Treatment and Desalination - Ahmad Kayvani Fard (14603387) (2018)
Inorganic membrane science and technology is an attractive field of membrane separation technology, which has been dominated by polymer membranes. Recently, the inorganic membrane has been undergoing rapid development and innovation. Inorganic membranes have the advantage of resisting harsh chemical cleaning, high temperature and wear resistance, high chemical stability, long lifetime, and autoclavable. All of these outstanding properties made inorganic membranes good candidates to be used for water treatment and desalination applications. This paper is a state of the art review on the synthesis, development, and application of different inorganic membranes for water and wastewater treatment. The inorganic membranes reviewed in this paper include liquid membranes, dynamic membranes, various ceramic membranes, carbon based membranes, silica membranes, and zeolite membranes. A brief description of the different synthesis routes for the development of inorganic membranes for application in water industry is given and each synthesis rout is critically reviewed and compared. Thereafter, the recent studies on different application of inorganic membrane and their properties for water treatment and desalination in literature are critically summarized. It was reported that inorganic membranes despite their high synthesis cost, showed very promising results with high flux, full salt rejection, and very low or no fouling. Other Information Published in: Materials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ma11010074